Dynamic characteristics of sulfur, iron and phosphorus in coastal polluted sediments, north China. (December 2016) - Sun, Qiyao; Sheng, Yanqing; Yang, Jian; Di Bonito, Marcello; Mortimer, Robert J.G.
Abstract: The cycling of sulfur (S), iron (Fe) and phosphorus (P) in sediments and pore water can impact the water quality of overlying water. In a heavily polluted river estuary (Yantai, China), vertical profiles of fluxes of dissolved sulfide, Fe 2+ and dissolved reactive phosphorus (DRP) in sediment pore water were investigated by the Diffusive Gradients in Thin films technique (DGT). Vertical fluxes of S, Fe, P in intertidal sediment showed the availability of DRP increased while the sulfide decreased with depth in surface sediment, indicating that sulfide accumulation could enhance P release in anoxic sediment. In sites with contrasting salinity, the relative dominance of iron and sulfate reduction was different, with iron reduction dominant over sulfate reduction in the upper sediment at an intertidal site but the reverse true in a freshwater site, with the other process dominating at depth in each case. Phosphate release was largely controlled by iron reduction. Highlights: Fluxes of sulfide, Fe 2+ and phosphorus in sediments were investigated. Sulfide accumulation could enhance phosphorus release in anoxic sediment. Phosphate release was largely controlled by iron reduction. Iron and sulfate reduction controlled the flux of Fe 2+, sulfide and phosphate. Abstract : The relative rates of microbial iron and sulfate reduction controlled the flux of Fe 2+, sulfide and phosphate to the pore waters in coastal sediments.